IMPACT OF CHILDHOOD EPILEPSY ON MENTAL DEVELOPMENT - Nurmatov Baxtiyorjon (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Childhood epilepsy represents a complex neurobiological disorder that frequently disrupts normative trajectories of cognitive maturation and psychological adaptation. The interplay between recurrent electrographic discharges, structural network remodeling, and pharmacological interventions generates cumulative developmental vulnerabilities that extend beyond seizure cessation. This longitudinal investigation evaluated the psychometric and neurodevelopmental outcomes of pediatric patients managed at a tertiary referral center. A prospective cohort design tracked clinical and neuropsychological parameters across three consecutive years, integrating standardized cognitive batteries, behavioral rating scales, and quantitative electroencephalographic mapping. Primary outcome measures encompassed working memory consolidation, executive functioning indices, and adaptive social cognition. Secondary analyses examined dose-dependent relationships between antiseizure medication regimens and cognitive velocity. The analytical framework incorporated multivariate regression modeling to isolate seizure frequency from treatment-related neurocognitive suppression. Results indicate that uncontrolled focal epileptiform activity correlates with a measurable decline in processing speed and verbal fluency, whereas generalized seizure patterns predominantly impair sustained attention and inhibitory control. Early intervention protocols incorporating cognitive rehabilitation modalities demonstrate partial mitigation of developmental regression. These findings establish that chronological seizure control alone remains insufficient for preserving optimal neurodevelopmental trajectories. Comprehensive management frameworks must integrate neuropsychological surveillance alongside conventional epileptological monitoring to address the multifactorial nature of developmental compromise. The study provides empirical evidence supporting routine cognitive screening in pediatric epilepsy clinics, emphasizing the necessity of individualized therapeutic adjustments that balance seizure suppression with neurocognitive preservation.